Long-term institutional investors and climate change news Beta - Hossain, Ashrafee; Masum, Abdullah-Al; Benkraiem, Ramzi (Journal of Corporate Finance, 2024)
We predict and confirm that long-term institutional investors (LTIOs) play an important role in mitigating the negative market perceptions of US stocks following mainstream print media coverage of climate change. We observe a stronger effect of LTIOs for companies that lack corporate social responsibility and have less diverse and more co-opted boards. Overall, these findings indicate that the US equity market views LTIOs as effective monitors who can help guide companies facing climate risks toward a more sustainable trajectory.